Can markets support smallholder adoption of a food safety technology? Aflasafe in Kenya - Hoffmann, Vivian; Kariuki, Sarah; Pieters, Janneke; Treurniet, Mark (International Food Policy Research Institute, 2019)
In this paper, we test the impact of a simulated market premium for food safety, and of bundling rainfall insurance with an aflatoxin-reducing technology (Aflasafe KE01), on smallholder farmers’ adoption of this technology. To identify these impacts, we conducted a randomized trial through which farmers in one of the most aflatoxin-affected regions in the world were given the opportunity to purchase Aflasafe under experimentally varied market conditions. Half of 152 pre-existing producer groups were assigned to a market linkage treatment and offered a premium price for the maize they aggregated if it conformed to the East African aflatoxin standard. The market linkage treatment was cross-cut with a bundled insurance treatment, in which Aflasafe could only be purchased together with an actuarily fair rainfall index insurance product designed to insure against maize losses due to unfavorable weather conditions during the growing period. Farmers not assigned to the bundled insurance treatment who purchased Aflasafe were able to purchase the same insurance separately.